Jenis-Jenis Pendekatan sebagai Strategi Inovatif bagi Peserta Didik dalam Pembelajaran IPS - Mukhlisin Nata Hudin; Junadhan Syapa Widyaksa; Sabitah Salwa Alfarras; Sani Safitri (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Social science is a field that explores social behavior and activities in human life. The learning approach for students in social science has many types of approaches, therefore this article will describe the types of learning approaches for students in social science. This research uses descriptive qualitative, the research source is a literature review obtained from articles, journals, books, research reports, cofference proceedings, theses and so on. In this article, it is explained about 4 approaches that are carried out in social studies learning, namely Thematic, Scientific, Interdisciplinary, and Constructivist Approaches which are explained in detail in the content of the article. Overall, the application of various innovative approaches to social studies learning is important to create a more interesting, relevant and interactive learning experience. By using the right methods, social studies not only improves the quality of education, but also prepares young people with 21st century skills such as critical thinking, collaboration, communication and creativity. This is very relevant in facing challenges in the era of globalization.